LEGAL PROTECTION OF CHILD VICTIMS CONCLUSION THAT EXPERIENCES PREGNANCY (Study Decision Number: 234/Pid.Sus/2022/PN.Srg) - Kartika, Devi; Rofiana, Reine (Southeast Asian Journal of Victimology, 2023)
Losses caused by the crime of having intercourse with a child who is pregnant Sexual intercourse with a child will certainly have a serious physical and psychological impact in the future. With legal protection, the main reference for protection is in the form of compensation, restitution, and health assistance for him. The problems studied in this study are legal protection for child victims of intercourse who experience pregnancy and efforts to fulfill the right of restitution in law enforcement in cases of intercourse that experience pregnancy (Study of Decision Number: 234/Pid.Sus/2022/PN.Srg.). In this study, researchers used two theories: the first is the theory of legal protection, and the second is the theory of law enforcement. This type of research uses qualitative, normative, and juridical research. This research is descriptive and analytical. The data sources used in this research are secondary data sources, which are then analyzed qualitatively. The results of this study show that there is no legal protection for child victims of sexual intercourse. This can be seen by the fact that the victim did not receive compensation and reimbursement for transportation costs, the victim did not receive psychological assistance and social rehabilitation, the victim did not receive legal counsel, the child victim of sexual intercourse during the examination did not get a separate room from the adults for the examination of the childvictim of sexual intercourse, the Serang Police are still in the same place as adults, and there is no restitution for victims in the decision. Suggestions in this study should be that the Serang State Prosecutor's Office in this case be proactive and question the reasons the panel of judges in the trial did not mention the convict's obligation to provide restitution rights during the trial against the defendant DYS (49). This is because it is clear that the application is contained in the prosecution file and there is a request from the victim.